THE SILENT DRIVERS OF EARLY MARRIAGE: HOW PARENTAL SUPPORT OUTWEIGHS KNOWLEDGE AND ATTITUDE - Quraisy, Reihanatu; Kusumawardani, Devi Arine (UNIVERSITAS AIRLANGGA, 2025)
Background: Early marriage is still one of the problems affecting the health of society in Indonesia. The application for marriage dispensation in Jember Regency increases yearly; in 2020, Jember Regency was ranked second nationally. The purpose of this study was to determine the description of knowledge, attitudes and support of parents who have children who marry early in Silo District, Jember Regency. Method: This study is a descriptive study with a quantitative approach in Silo District, Jember Regency from July 2024 - August 2024. The population of this study was 77 parents who had children who married early in Silo District, Jember Regency. The sample was obtained from 75 because two people did not meet the inclusion criteria. The data were then analyzed univariately with a descriptive method before being presented in text and table form. Result: The results showed that 47 respondents (62.7%) had poor knowledge about the impact of early marriage, while only 28 respondents (37.3%) had good knowledge. Parents' attitudes towards early marriage were mainly negative, with 41 respondents (54.7%) having negative attitudes, and 34 respondents (45.3%) having positive attitudes. Conclusion: Most parents support children who marry early, with 52 respondents reporting high support, while 23 respondents reported low support.